German Verse from the 12th to the 20th Century in English Translation - Thomas, J.W (UNC Studies in the Germanic Languages and Literatures, 1963)
This anthology presents in English verse translation a selection of the best of German poetry, together with discussions of the chief authors and literary periods and brief explications of the individual poems. Taking the reader from the Minnesingers' songs of courtly love to Goethe and Rilke, this volume gives an excellent introduction to eight centuries of German poetry.